Ibn Rushd’s Rationality and Its Relevance for Malay Muslim Identity in Riau - Alpin Harianto; Dian Nur Anna (Al-Munawwarah: Journal of Islamic Education, 2025)
This study is motivated by the importance of examining the relevance of the Muslim philosopher Ibn Rushd’s thought in shaping the Islamic Malay identity in Riau, which is currently facing the challenges of globalization, modernization, and shifting cultural values. The main problem addressed in this research is how Ibn Rushd’s concept of rationality is understood and integrated into the formation of religious and cultural character within the Islamic Malay community in Riau. This research employs a library research method by analyzing Ibn Rushd’s works alongside scholarly literature related to Islamic Malay identity. The findings reveal that Ibn Rushd’s idea of harmonizing reason and revelation aligns with the principle of “adat bersendikan syarak, syarak bersendikan Kitabullah” in the Riau Malay tradition. The rationality promoted by Ibn Rushd strengthens the intellectual framework of the Islamic Malay community, fostering a more moderate, critical, and responsive attitude toward contemporary challenges. This study contributes to Islamic and cultural studies by offering a philosophical framework that integrates classical Islamic rationality with local identity formation, thereby enriching discussions on how Muslim communities can sustain religious and cultural identity while engaging constructively with modern intellectual developments.